ANALISIS PERILAKU GENERASI MILENIAL DALAM PENGAMBILAN KEPUTUSAN INVESTASI SAHAM DI MASA PANDEMI COVID-19 - Devindha Fitria Mahafani; Diah Maya Puspa; Nurul Khasanah; Siti Wulandari; Vivi Andriani (Academica: Journal of Multidisciplinary Studies, 2021)
This study aims to analyze the behavior of the millennial generation in making stock investment decisions during the Covid-19 pandemic. This research method uses a qualitative method with a case study approach. The research subjects were four people who were included in the millennial generation category who were under 30 years old and domiciled in Solo Raya. The results of this study indicate that the behavior of investors in making stock investment decisions is based on the declining stock price trend due to the Covid-19 pandemic, influenced by the herding bias factor, namely following the actions or suggestions of others, but also analyzing the company's performance by looking at its financial statements.Keywords: Covid-19; Investor Behavior; Investment Decisions; Millenial Generation